Prevalence of Irritable Bowel Syndrome among Medical Students of Puerto Rico - Ramírez-Amill, Reinaldo; Torres, Esther A. (Puerto Rico Health Sciences Journal, 2021)
Objective: Irritable bowel syndrome (IBS) is characterized by chronic abdominal pain and altered bowel habits. A high prevalence has been reported in medical students around the globe. This study aimed to investigate the prevalence of IBS and associated risk factors in medical students in Puerto Rico (PR). Methods: A cross sectional study was conducted in a sample of medical students from first to fourth year currently enrolled at the University of PR School of Medicine. Participants completed a self-administered, anonymous questionnaire that contained questions about general socio-demographic data, lifestyle habits, degree of subjective psychological stress and the Rome III criteria: IBS Module. Results: 314 medical students were included for analysis. The mean age was 24.8±3.25; 48.1% were females. The prevalence of IBS was 36.3%. Among the IBS subjects, 78 (24.8%) were classified as IBS mixed. Family history of IBS and psychological stress were significantly associated to IBS (p<0.05), whereas cigarette smoking was found to be protective for IBS (OR = 0.26 + .17, P=.04). Conclusion: This is the first study to describe the prevalence of IBS in medical students in PR. A higher prevalence of IBS was found as compared to that reported for medical students in other countries. Additional studies aimed at estimating the impact of IBS on quality of life and academic performance of the medical students are essential.